Helping people with a mental illness obtain work: the Health Optimisation Program for Employment. (August 2016) - Castle, David; Crosse, Caroline; Morgain, Dea; McDowell, Caitlin; Rossell, Susan; Thomas, Neil; Phillipou, Andrea; Gilbert, Monica; Moore, Gaye; Fossey, Ellie; Harvey, Carol
Objective: Inclusion in work and education remains problematic for many people with a mental illness. We describe a structured programme – the Health Optimisation Program for Employment – that supported people with a mental illness to gain employment or commence studies. Method: Twenty hours of the Health Optimisation Program for Employment were delivered to 600 individuals. Participants were asked to complete an evaluation survey encompassing vocational status and ratings of self-efficacy. Results: Of the 364 participants who completed the baseline assessment, 168 responded to the evaluation survey 6 months after the delivery of the Health Optimisation Program for Employment. Of these, 21.5% had started a new job, while a further 42.8% were either volunteering or studying. Satisfaction with the programme was high and self-efficacy ratings improved significantly over the short term only. Conclusions: The Health Optimisation Program for Employment requires further evaluation using rigorous scientific methodology but these initial results are encouraging in terms of vocational attainment for people with a mental illness, in the Australian context.